The impact of transformational leadership, Islamic spirituality, organizational commitment and citizenship behavior on employee performance: An empirical study of Islamic insurance (TAKAFUL) industry in Malaysia / Fares Djafri - Fares , Djafri (2017)
In the service sectors such as insurance and Islamic insurance (Takaful), employee behaviour can have a significant impact on an organisation’s performance, success, and service quality. It is observed that the attitude of takaful agents is considered a vital factor that influence customers to maintain and retain their policies and products. Agents of Islamic insurance (Takaful) are in charge of the business vision and philosophy of giving quality information, advice to clients and promoting a company’s products. Therefore, a key concern of takaful operators should be how to attain positive attitudes from their employees and motivate them to be more committed, productive, and effective within their organisation. This issue has raised a critical research agenda that requires attention to identifying and testing the critical factors which are recommended for the successful and effectiveness of an organisation and investigate their impact on employee performance. As such, this empirical study explores the impact of various factors on the performance of takaful agents in Malaysia. More specifically, this study explores the role of transformational leadership, Islamic spirituality, organisational commitment, and Organisational Citizenship Behaviour (OCB) in enhancing organisational effectiveness and employee performance of the Malaysian takaful industry. A theoretical framework was developed based on a review of past literature. Accordingly, the framework was tested using primary data obtained from a survey of 513 employees/agents in Klang Valley, which is considered the hub of all takaful activities and contains maximum takaful agencies compared to the rest of Malaysia. Data obtained from respondents were analysed using descriptive analysis, exploratory and confirmatory factor analysis with two statistical analysis software application: SPSS and AMOS. After the measurement model has achieved acceptable results and proved to have goodness-of-fit, the next step was to test the full structural model and the proposed research hypotheses as postulated in the model. A total of twelve hypotheses were proposed in this study based on extensive review of the literature, out of which, eleven were supported. The findings of this research revealed that job performance appeared to have been directly and indirectly influenced by all constructs. All direct hypotheses proposed in the present study were supported except the structural path between Islamic spirituality and employee performance. Further, it was revealed that organisational commitment partially mediated the relationship between transformational leadership and OCB, and between Islamic spirituality and OCB. In addition, OCB partially mediated the relationship between transformational leadership and job performance, while fully mediated the relationship between Islamic spirituality and job performance. The findings of this research would have implications for policy makers and top management in the human resources development of service organisation sector, particularly the takaful industry. Policy makers and top management can use the empirical findings of this research as a valuable input to justify their efforts in developing and implementing appropriate learning and performance improvement initiatives.